A variety of Fourier-invariant Gaussian beams - Victor Kotlyar; Alexey Kovalev; Alexey Porfirev (Компьютерная оптика, 2018)
A two-parameter family of astigmatic elliptical Gaussian (AEG) optical vortices is found, which are free space modes up to scale and rotation. We calculate the total normalized orbital angular momentum of AEG vortices, which can be integer, fractional and zero, and which is equal to the algebraic sum of two terms corresponding to the contribution of the vortex and astigmatic components of the light field. In any transverse plane, such a beam has an isolated n-fold degenerate intensity null on the optical axis (an optical vortex) embedded into an elliptical Gaussian beam. In addition to the quadratic elliptical phase, the beam has a phase of a cylindrical lens rotated by an angle of 45 degrees relative to the principal axes of the Gaussian beam intensity ellipse.